Madurese Society's Rejection of the Heredity of Children of Adultery in the Context of Marriage from the Perspective of Islamic Legal Anthropology - Syahrullah Asyhari; Moh. Muhibbin; Shofiatul Jannah (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
One of the strong beliefs among the Madurese community is the inevitability that the child of adultery will inherit the habits of the biological father who committed adultery. This study is called the heredity of the child of adultery. This view is rooted in a tradition that directly links the nature and character of children with heredity. This study uses an empirical legal method with a legal anthropology approach to examine in depth the practice of Madurese rejection of children resulting from adultery (children of adultery). Primary legal materials were obtained from observations and interviews with the Banyubunih Village community. Secondary legal materials were obtained from concepts relevant to the issues in the study. The results of this study identified that the Banyubunih community considers heredity as a very influential factor in determining the nature, character, and behavior of individuals, especially in children of adultery. This belief is based on the principles of biological determinism and hereditary essentialism, which argue that negative traits and deviant behavior are inherited through the "dirty blood" of parents. As a result, children born from extramarital relationships are placed in the lowest social position, without the opportunity to demonstrate their morals and behavior independently